The Brain Network Underlying the Recognition of Hand Gestures in the Blind: The Supramodal Role of the Extrastriate Body Area - Kitada, Ryo (J Neurosci, 2014)
The visual perception of others' body parts is critical for understanding and imitating their behavior. The visual cortex in humans includes the extrastriate body area (EBA), which is a large portion of the occipitotemporal cortex that is selectively responsive to visually perceived body parts. Previous neuroimaging studies showed that the EBA not only receives sensory inputs regarding others' body information but also receives kinesthetic feedback regarding one's own actions. This finding raised the possibility that the EBA could be formed via nonvisual sensory modalities. However, the effect of visual deprivation on the formation of the EBA has remained largely unknown. Here, we used fMRI to investigate the effect of vision loss on the development of the EBA. Blind and sighted human subjects performed equally well in a haptic-identification task involving three categories of objects (hand shapes, toy cars, and teapots). The superior part (i.e., the middle temporal gyrus and angular gyrus) of the EBA and the supramarginal gyrus showed greater sensitivity to recognized hand shapes than to inanimate objects, regardless of the sensory modality and visual experience. Unlike the superior part of the EBA, the sensitivity of the inferior part (i.e., the inferior temporal sulcus and middle occipital gyrus) depended on visual experience. However, this vision-dependent sensitivity explained minor individual differences in hand-recognition performance. These results indicate that nonvisual modalities drive the development of the cortical network underlying the recognition of hand gestures with a node in the visual cortex.